Strategi Pembelajaran Inkuiri (SPI) dan Penerapannya dalam Pembelajaran Bahasa Indonesia - Elniyeti, Elniyeti (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2017)
This writing aims to explain Learning Strategy Inquiry (SPI) and its application in learning Indonesian. Learning is not just memorizing and not just remembering, but learning is a process marked by a change in a person. Inquiry learning strategies will help teachers bring students to understand the concept of subject matter. In addition, it will also bring students in learning that emphasizes the critical and analytical thinking process to seek and find answers to a questionable problem for learning outcomes. Inquiry learning strategy is a student centered learning strategy that is very demanding of student activities. Initially this inquiry learning strategy is widely applied in the natural sciences (natural science). But demilkian, social sciences education experts adopted inquiry strategies that later became called social inquiry. From the characteristics of inquiry as described above, the application of social inquiry in Indonesian language learning is not different from the application of inquiry in general. The difference lies solely in the problem under study. Thus, the application of inquiry learning strategies in learning Indonesian, will certainly examine the subject matter in the Indonesian language